(untitled) (ModaPalavra e-periódico, 2026)
This article aims to examine Black male elegance, drawing on the concept of technology of blackness and the technical nuances of dandyism. It seeks to investigate the structuring of the regime of visibility of the Black dandy, as well as to outline the constitution of his ethical-poetic formation. To this end, we use the notion of Afrofabulation as a theoretical tool to reflect on the expressive value of bodily gestures and the individuation of nuance through artefacts and technical devices. In the context of the intersections between Blackness and dandyism, we adopt an interdisciplinary operational approach that allows us to think about the relations involving fashion, aesthetics, history, and anthropology. The first section of the analysis is dedicated to the exploration of gesture and bodily techniques, with the aim of integrating strategies of body stylization into the dynamic model of Blackness. For this examination, we draw on the writings of Marcel Mauss (2021), André Leroi-Gourhan (1964), Yves Citton (2012), Marielle Macé (2016), Albert Camus (2012) and Abdias Nascimento (1982). In the second section, we focus on the processes of reception, transmission and historical transgression of dandyism in diasporic manifestations. Based on sartorial anarchy, we investigate the subversion of colonial subjugation strategies, revisiting the meanings of fabulation and ethnicity to reflect on the concept of “Afro-fabulation,” with reference to Gilles Deleuze (2012), Achille Mbembe (2014) and Stuart Hall (2006). Our purpose is to think about the formation of the ethos of the elegant black man, understanding his identity construction based on the heroic action of modelling appearance, conceived as an act of civic freedom.